Performance of serum biomarkers reflective of different pathogenic processes in systemic sclerosis-associated interstitial lung disease. - Györfi, Andrea Hermina; Filla, Tim; Dickel, Nicholas; Möller, Florian; Li, Yi Nan; Bergmann, Christina; Matei, Alexandru-Emil; Harrer, Thomas; Kunz, Meik; Schett, Georg; Distler, Jörg H.W. (Rheumatology, 2024)
OBJECTIVE: Interstitial lung disease (ILD) is the leading cause of mortality in SSc. Novel biomarkers are crucial to improve outcomes in SSc-ILD. We aimed to compare the performance of potential serum biomarkers of SSc-ILD that reflect different pathogenic processes: KL-6 and SP-D (epithelial injury), CCL18 (type 2 immune response), YKL-40 (endothelial injury and matrix remodelling) and MMP-7 (ECM remodelling). METHODS: Baseline and follow-up serum samples from 225 SSc patients were analysed by ELISA. Progressive ILD was defined according to the 2022-ATS/ERS/JRS/ALAT guidelines. Linear mixed models and random forest models were used for statistical analyses. RESULTS: Serum levels of KL-6 [MD 35.67 (95% CI 22.44-48.89, P < 0.01)], SP-D [81.13 (28.46-133.79, P < 0.01)], CCL18 [17.07 (6.36-27.77, P < 0.01)], YKL-40 [22.81 (7.19-38.44, P < 0.01)] and MMP-7 [2.84 (0.88-4.80, P < 0.01)] were independently associated with the presence of SSc-ILD. A machine-learning model including all candidates classified patients with or without ILD with an accuracy of 85%. The combination of KL-6 and SP-D was associated with the presence [0.77 (0.53-1.00, P' <0.01)] and previous progression of SSc-ILD [OR 1.28 (1.01-1.61, P' =0.047)]. Higher baseline levels of KL-6 [OR 3.70 (1.52-9.03, P < 0.01)] or SP-D [OR 2.00 (1.06-3.78, P = 0.03)] increased the odds of future SSc-ILD progression, independent of other conventional risk factors, and the combination of KL-6 and SP-D [1.109 (0.665-1.554, P < 0.01)] showed improved performance compared with KL-6 and SP-D alone. CONCLUSION: All candidates performed well as diagnostic biomarkers for SSc-ILD. The combination of KL-6 and SP-D might serve as biomarker for the identification of SSc patients at risk of ILD progression.
EVALuna2:538826